1988
DOI: 10.1073/pnas.85.19.7265
|View full text |Cite
|
Sign up to set email alerts
|

Phosphocreatine, an intracellular high-energy compound, is found in the extracellular fluid of the seminal vesicles in mice and rats.

Abstract: High levels of phosphocreatine, a compound known to serve as an intracellular energy reserve, were found in the fluid contained in seminal vesicle glands. The concentrations of phosphocreatine in the extracellular fluid in the mouse and rat were found to be 5.6 ± 1.6 and 2.2 ± 0.8 ,umol/g, respectively, which are higher than the intracellular levels reported for smooth muscles. The creatine concentrations in the seminal vesicular fluid from these two species were 22.8 ± 3.1 and 13.0 ± 5.3 ,umol/g, respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

1990
1990
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 30 publications
1
17
0
Order By: Relevance
“…Furthermore, female rats showed much smaller elevations in urinary creatine after 444 being given the same doses of cadmium as the male animals (Nicholson et al 1989). The testis is known to contain very high concentrations of creatine but only about 7% as creatine phosphate (Lee et al 1988). This is in contrast to other tissues such as muscle, which utilise creatine phosphate as an energy source and where more than 30% is present as creatine phosphate.…”
Section: Introductionmentioning
confidence: 92%
“…Furthermore, female rats showed much smaller elevations in urinary creatine after 444 being given the same doses of cadmium as the male animals (Nicholson et al 1989). The testis is known to contain very high concentrations of creatine but only about 7% as creatine phosphate (Lee et al 1988). This is in contrast to other tissues such as muscle, which utilise creatine phosphate as an energy source and where more than 30% is present as creatine phosphate.…”
Section: Introductionmentioning
confidence: 92%
“…As shown by testicular Hr-MAS 1 H-NMR spectroscopy, testicular tissue has high concentrations of creatine. In fact, creatine concentration in rat testes and seminal fluid is significantly higher than in blood (Lee et al, 1988). The finding indicated that sperm cells require a high concentration of creatine to maintain their viability and function.…”
Section: Discussionmentioning
confidence: 69%
“…Nonetheless, a low liver creatinine level is thought to be of more significance because this shows that the metabolic reactions are not occurring in their full capacity in the liver and thus hinting towards liver disease [53]. Some reasons why the liver might have high creatinine levels is a diet that has a lot of meat and meat products in it, late stage of muscular dystrophy, prerenal azotemia and Myasthenia gravis [52].…”
Section: Discussionmentioning
confidence: 99%